2018
DOI: 10.1158/1541-7786.mcr-18-0321
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Myofibroblasts Promote Tumor Growth via Mitochondrial ROS–Activated TGFβ Signaling

Abstract: Fibroblasts are a key stromal cell in the tumor microenvironment (TME) and promote tumor growth via release of various growth factors. Stromal fibroblasts in cancer, called cancer-associated fibroblasts (CAF), are related to myofibroblasts, an activated form of fibroblast. While investigating the role of stroma fibroblasts on radiation-related carcinogenesis, it was observed following long-term fractionated radiation (FR) that the morphology of human diploid fibroblasts changed from smaller spindle shapes to l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…ROS can be derived from different sources, including the mitochondria electron transport chain, xanthine oxidase, the cytochrome P450 system, uncoupled nitric oxide synthase, and myeloperoxidase. ROS also mainly comes from two main parts, mitochondrial and NADPH oxidase after radiation ( Bedard and Krause, 2007 ; Bhattacharyya et al., 2014 ; Cho et al., 2017 ; Pei et al., 2017 ; Kawamura et al., 2018 ; Sakai et al., 2018 ; Shimura et al., 2018 ; Mortezaee et al., 2019 ). To explore the origin of ROS induced by 1α,25(OH) 2 D 3 , both NADPH oxidase inhibitors, DPI and Apocynin, and the mitochondrial membrane potential were used to determine the source of ROS ( Bedard and Krause, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…ROS can be derived from different sources, including the mitochondria electron transport chain, xanthine oxidase, the cytochrome P450 system, uncoupled nitric oxide synthase, and myeloperoxidase. ROS also mainly comes from two main parts, mitochondrial and NADPH oxidase after radiation ( Bedard and Krause, 2007 ; Bhattacharyya et al., 2014 ; Cho et al., 2017 ; Pei et al., 2017 ; Kawamura et al., 2018 ; Sakai et al., 2018 ; Shimura et al., 2018 ; Mortezaee et al., 2019 ). To explore the origin of ROS induced by 1α,25(OH) 2 D 3 , both NADPH oxidase inhibitors, DPI and Apocynin, and the mitochondrial membrane potential were used to determine the source of ROS ( Bedard and Krause, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since individual radiation sensitivity may influence dose assessment, biodosimetry may be able to screen a highly radiation sensitive population in large nuclear incidents. We previously reported that excessive mitochondrial ROS activates transforming growth factor-beta (TGF-β) signaling, thereby inducing myofibroblast differentiation and facilitating tumor growth through tumor microenvironment formation (TME) formation [35]. ROS-mediated mitochondrial damage is associated with TME via fibroblast activation [35].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that excessive mitochondrial ROS activates transforming growth factor-beta (TGF-β) signaling, thereby inducing myofibroblast differentiation and facilitating tumor growth through tumor microenvironment formation (TME) formation [35]. ROS-mediated mitochondrial damage is associated with TME via fibroblast activation [35]. Consequently, use of oxidative biological markers serves both radiation dose assessment and evaluation of radiation risks for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is able to concentrate in intracellular compartments, mainly in fibroblasts, hepatocytes, phagocytic cells, and white blood cells, where concentrations reach up to 321 µM (240 µg/mL), approximately 1000 times that of C max . Shimura et al [21] reported that mitochondrial ROS of myofibroblasts induced by radiation activated TGF β signaling and promoted tumor growth. Numerous studies provide evidence that chronic inflammation increases the risk of cancer [22,23].…”
Section: Discussionmentioning
confidence: 99%